Fusion of cuckoo search and hill climbing techniques based optimal forwarder selection and detect the intrusion - Sai Madhuri; Jitendranath Mungara (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
The cuckoo search (CS) technique is applying to discover the optimal route from source to destination. The main objective of this work is to offer suitable solutions for getting better the optimal routing and communicating the data via reliable sensor nodes. This CS optimization method not capable for managing the diversity of the solutions. To solve this issue, we use the CS technique to hybridize it with the hill climbing (HC) technique to minimize the probability of early convergence. This approach introduces a fusion of CS and HC techniques (CSHC) based optimal forwarder selection and detect the Intrusion in wireless sensor network (WSN) . Here, a Bayesian thresholding method is predict the received signal strength and link reliability parameter for identifying intrusion in the network. The hill - climbing technique is able to attain the best solutions in a smaller period than other local search techniques. In CSHC, the optimal forwarderis selection by fitness function. This fitness function is computed based on sensor node lifetime, sensor link reliability, and buffer availability. In this app roach, the experimental results suggest that the CSHC for improving 35% throughput and minimizes the 23.52% packet lossescompared to the baseline approaches.